Oral Administration of Polymer Hyaluronic Acid Alleviates Symptoms of Knee Osteoarthritis: A Double-Blind, Placebo-Controlled Study over a 12-Month Period - Tashiro, Toshiyuki (The Scientific World Journal, 2012)
This study was conducted to investigate the efficacy of oral hyaluronic acid (HA) administration for osteoarthritis (OA) in knee joints. Sixty osteoarthritic subjects (Kellgren-Lawrence grade 2 or 3) were randomly assigned to the HA or placebo group. The subjects in the HA group were given 200 mg of HA once a day everyday for 12 months, while the subjects in the placebo group were given placebo. The subjects in both groups were requested to conduct quadriceps strengthening exercise everyday as part of the treatment. The subjects' symptoms were evaluated by the Japanese Knee Osteoarthritis Measure (JKOM) score. The symptoms of the subjects as determined by the JKOM score improved with time in both the HA and placebo groups. This improvement tended to be more obvious with the HA group, and this trend was more obvious with the subjects aged 70 years or less. For these relatively younger subjects, the JKOM score was significantly better than the one for the placebo group at the 2nd and 4th months after the initiation of administration. Oral administration of HA may improve the symptoms of knee OA in patients aged 70 years or younger when combined with the quadriceps strengthening exercise.